Testing the consistency of spatio-temporal patterns of flight activity in the stored grain beetles Tribolium castaneum (Herbst) and Rhyzopertha dominica (F.). (May 2017) - Daglish, Gregory J.; Ridley, Andrew W.; Reid, Robin; Walter, Gimme H.
Abstract: Many studies have been published on the flight activity of stored grain beetles in temperate regions, but few have focussed on tropical and sub-tropical regions. The spatio-temporal patterns of flight activity of Tribolium castaneum (Herbst) and Rhyzopertha dominica (F.) were quantified in a grain growing district on the Tropic of Capricorn in central Queensland, Australia. Nine traps baited with aggregation pheromone lures were monitored at 2-wk intervals (fortnightly) for 1 year along a 28.4 km linear transect that included sites at bulk grain depots and sites away from stored grain. Beetles of both species were trapped every fortnight during the study. The spatio-temporal patterns of flight activity differed greatly across the two species, as predicted from studies elsewhere. Rhyzopertha dominica was widespread across the landscape, as the mean trap catch of this species was equal in depot and non-depot traps. In contrast, T. castaneum was more frequently trapped in depot traps than non-depot traps during the colder months, but was much more widespread across the landscape during the summer months. Tribolium castaneum also showed a clear mid-summer peak in flight activity, whereas R. dominica flight activity was highly variable throughout the study. In general, our results reveal patterns that are consistent with those found for T. castaneum and R. dominica in southern Queensland. The contrasting spatio-temporal patterns of flight activity of R. dominica and T. castaneum show that species-specific approaches may be needed to manage these pests and that the spatio-temporal dynamics of resistance genes may differ across these species. Highlights: Flight activity of two grain pests was studied in north eastern Australia. Rhyzopertha dominica was widespread across the farming landscape. Tribolium castaneum was aggregated around grain storages except during summer. Tribolium castaneum numbers peaked in mid-summer. Rhyzopertha dominica numbers were much more variable.